Enhanced Bacteriocin Production by Pediococcus pentosaceus 147 in Co-culture With Lactobacillus plantarum LE27 on Cheese Whey Broth - Gutiérrez-Cortés, Carolina; Suarez, Héctor; Buitrago, Gustavo; Nero, Luis Augusto; Todorov, Svetoslav Dimitrov (Frontiers in Microbiology, 2018)
The production of bacteriocins by lactic acid bacteria (LAB) has been of wide interest in the food industry due to their potential application in biopreservation. The production of bacteriocins is usually low in single strain fermentation, but can improve when the bacteriocinogenic strain is cultured in association with another bacteria. The present work aims to evaluate the growth and production of bacteriocins by Pediococcus pentosaceus 147 (bacteriocinogenic strain) in co-culture with Lactobacillus plantarum LE27 (inducer strain) using a culture medium based on cheese whey (CW). Strains were inoculated in co-culture in a CW broth at 7.24 Log CFU/mL of initial concentration of P. pentosaceus 147 and incubated at 37oC. Bacteriocin production was measured after 24 hours by the critical dilution method, biomass was measured by plating on MRS agar (1% aniline blue), and mono-culture was used as a control. The titers of bacteriocins produced by P. pentosaceus 147 in mono-culture were 19,200 AU/mL lower than those obtained in co-culture with Lb. plantarum LE27 at 51,200 AU/ml. The effect of the addition of the inducer strain at different times of incubation (3, 6, 9 and 12 hours) was evaluated, with the addition of the induction factor at the beginning of the incubation of P. pentosaceus 147 generating the highest bacteriocin activity. This study shows the potential of inducing bacteriocinogenesis using co-cultures of strains of the genera Pediococcus and Lactobacillus using alternative substrates such as cheese whey.